2022
DOI: 10.1111/1758-2229.13061
|View full text |Cite
|
Sign up to set email alerts
|

Cloacimonadota metabolisms include adaptations in engineered environments that are reflected in the evolutionary history of the phylum

Abstract: Phylum Cloacimonadota (previously Cloacimonetes, WWE1) is an understudied bacterial lineage frequently associated with engineered and wastewater systems. Cloacimonadota members were abundant and diverse in metagenomic datasets from a municipal landfill, prompting an examination of phylogenetic relationships, metabolic diversity, and pangenomic dynamics across the phylum, based on the 30 publicly available genomes and 24 new metagenome-assembled genomes (MAGs) from landfill samples. We found that Cloacimonadota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…To date, members of Cloacimonadota have not been enriched in any marine environment, and previous reports of their presence are based on incubations and metagenomic analyses [ 20 , 28 , 29 ]. Here, we report an increase in the cell density of Cloa-SY6, a member of Cloacimonadota , in a medium containing propionate (0.2 g L −1 ), indicating its ability to use this substrate.…”
Section: Resultsmentioning
confidence: 99%
“…To date, members of Cloacimonadota have not been enriched in any marine environment, and previous reports of their presence are based on incubations and metagenomic analyses [ 20 , 28 , 29 ]. Here, we report an increase in the cell density of Cloa-SY6, a member of Cloacimonadota , in a medium containing propionate (0.2 g L −1 ), indicating its ability to use this substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the results obtained for Euryarchaeota suggest that methanogenic archaea are under a strong selective pressure and harbor a large amount of genetic variability. The metabolic roles of species belonging to Candidatus Cloacimonetes and Synergistetes are still not completely clear, however, it was previously reported that some of them are characterized by acetogenesis [ 98 ], or can compete for acetate utilization with Methanosaeta [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, members of Cloacimonadota have not been enriched in any marine environment, and previous reports of their presence are based on incubations and metagenomic analyses 20,28,29 . Here, we report an increase in the cell density of Cloa-SY6, a member of Cloacimonadota , in a medium containing propionate (0.2 gL −1 ), indicating its ability to use this substrate.…”
Section: Resultsmentioning
confidence: 99%